2016
DOI: 10.5539/ass.v12n6p223
|View full text |Cite
|
Sign up to set email alerts
|

Life Skills Acquired in Relation to Teaching Methods Used Through Swimming Context

Abstract: This study aims: (1) to examine life skills acquired by students attending different levels of swimming courses.(2) To investigate the relation between teaching/learning methods used by swimming teachers and the level of life skills acquired. The population of this study were students who attended one of the three levels of the swimming courses in the Faculty of Physical Education /University of Jordan (n= 236). The sample of the study consisted of 142 students. Both "Life skills through swimming context scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Sport psychologists believe that sports are a vehicle for healthy development (Holt et al, 2008). Therefore, the swimming context can be a rich environment to help students develop such skills (Bayyat et al, 2016). Ay (2019) has revealed a moderate level of psychological skills for students enrolled in swimming classes.…”
Section: Introductionmentioning
confidence: 99%
“…Sport psychologists believe that sports are a vehicle for healthy development (Holt et al, 2008). Therefore, the swimming context can be a rich environment to help students develop such skills (Bayyat et al, 2016). Ay (2019) has revealed a moderate level of psychological skills for students enrolled in swimming classes.…”
Section: Introductionmentioning
confidence: 99%
“…The butterfly stroke is the most widely used in leisure and competitive swimming due to its speed. Research indicates that effective and interactive teaching techniques improve young people's life skills and development (Bayyat et al, 2016). Additionally, studies reveal that incorporating a swim board into swimming instruction might boost pupils' enthusiasm for learning how to swim freestyle (Sin & Hudayani, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The life skills questionnaire (Bayyat et al, 2016) consisted of (42) items reflecting five life skills which experts agreed to be the most appropriate and feasible to fulfill the aim of this study (see Appendix A). Bayyat et al, (2016) identified these skills as follows: (1) Communication: one's ability to express oneself verbally and nonverbally, expressing feelings, giving and receiving feedback without blaming.…”
Section: Life Skills Questionnairementioning
confidence: 99%
“…Subjects were (10) male deaf students who were at-tended to swimming courses level (1) in the Faculty of Physical Education at the University of Jor-dan, with mean age of (M age = 20.4 SD =1.35). After completing the Life skills through swimming context scale (Bayyat et al, 2016) and practical pre-test of free style swimming skills performance, subjects executed both physical practice of the free style swimming skills performance during a pro-gram conceited of eighteen sessions, 3 sessions a week, for 6-weeks, 60 mints per session, and life skills development dialogues program which focused on certain life skills (Communications, team-work, self-confidence/self-Esteem, problem solving and decision-making/responsibility).After 6-weeks all subjects completed a post life skills questionnaire which …”
mentioning
confidence: 99%